Chinese Archaeology (De Gruyter, 2001)
Chinese Archaeology is an annual periodical that publishes translations of the most important archaeological reports, preliminary findings, and research articles published in all major mainland Chinese journals that year. Chinese Archaeology is co-published by De Gruyter and the Institute of Archaeology of the Chinese Academy of Sciences. De Gruyter is responsible for the sales and distribution of the journal outside of China.